Features of acting performance in the Iraqi political theatrical show (Al-Academy, 2026)
It is very necessary for political theater to be within the space of every theatrical performance, because theater in general carries different values and cultures in all countries of the world. Theatrical performance played an important role in the theatrical presentation system, and the aesthetics of performance in the theatrical presentation, as well as theatrical performances, also multiplied. Which is presented on stage, its primary goal is to convey various ideas, messages, and topics to the audience in light of the events and circumstances that touched upon reality, as the recipient has become in dire need of watching theatrical performances that touch the political side, that address the ground of reality and motivate him toward the change and opposition that the audience needs in Iraqi society, Which reflects results and issues that have political dimensions and are addressed by proposing solutions that are embodied on the stage with complete freedom. The possibility of political theater has produced freedom of expression for real voices that are reflected and revealed to the public on the political stage in particular, and this is what the research deals with directly and based on what the researcher presented and answered the problem of her research. To the following question (What are the aesthetics of acting performance in the Iraqi political theatrical performance)The aim of the research: to explain the relationship of the features of theatrical performance to political theatre. The second chapter included two sections: the first: the features of theatrical performance in the global political theatre, and the second: the emergence of political theatre. As for the research sample, the purposive sample was adopted to serve the course of the research and its directions, and the most important results. theatrical performance was in dialogue with the known reality of the political events presented, and transcended its details. In doing so, it sought to beautify its image and make it better than it was historically.